A New Biphenyl from Nicotiana tabacum and its Anti-tobacco Mosaic Virus Activity - Liu, Chun-Bo; Zhao, Wei; Zhang, Feng-Mei; Shi, Xiao-Xi; Shen, Qin-Peng; He, Pei; Zhang, Tao; Liu, Zhi-Hua; Yang, Guang-Yu; Miao, Ming-Ming (Asian Journal of Chemistry, 2015)
A new biphenyl, tababiphenyl F (1) was isolated from the leaves of Nicotiana tabacum. Its structure was established on the basis of extensive spectroscopic analyses. Compound 1 was also tested for its anti-tobacco mosaic virus (anti-TMV) activity and its exhibited notable anti-tobacco mosaic virus activity with inhibition rate of 22.6 %.